Comorbidity of physical and anxiety symptoms in adolescent: functional impairment, self-rated health and subjective well-being - Balázs, Judit; Brunner, Romuald; Kaess, Michael (International journal of environmental research and public health, 2018)
Physical disorders and anxiety are frequently comorbid. This study investigates the characteristics of physical disorders, self-rated heath, subjective well-being and anxiety in adolescents. Data were drawn from the Saving and Empowering Young Lives in Europe cohort study. From 11 countries 11,230 adolescents, aged 14–16 years were included. Zung Self-Rating Anxiety Scale (SAS), WHO-5 Well-Being Index and five questions prepared for this study to evaluate physical illnesses and self-rated heath were administered. Anxiety levels were significantly higher in adolescents who reported having physical disability (p < 0.001, Cohen’s d = 0.40), suffering from chronic illnesses (p < 0.001, Cohen’s d = 0.40), impairments associated to health conditions (p < 0.001, Cohen’s d = 0.61), or reported poor to very poor self-rated health (p < 0.001, Cohen’s d = 1.11). Mediational analyses revealed no direct effect of having a chronic illness/physical disability on subjective well-being, but the indirect effects through higher levels of anxiety were significant. Functional impairment related to health conditions was both directly and indirectly (through higher levels of anxiety) associated with lower well-being. The co-occurrence of anxiety and physical disorders may confer a greater level of disability and lower levels of subjective well-being. Clinicians have to screen anxiety, even in a subthreshold level in patients with choric physical illness or with medically unexplained physical symptoms.
Gesehen am 04.03.2020